Rancang Bangun Robot Beroda Pemadam Api Menggunakan Metode Fuzzy Sugeno Berbasis Arduino - Herlambang Saputra; Indarto; Devinta Rosaline (Teknik Komputer Politeknik Negeri Sriwijaya, 2026)
Fire is one of the disasters that can cause significant losses, both material and nonmaterial. To reduce this risk, an automated system is needed that can respond quickly to fires. This robot is designed and built to automatically detect and extinguish fires using the Sugeno fuzzy logic method based on an Arduino microcontroller. The robot system is equipped with a flame sensor to detect the presence of fire and an ultrasonic sensor for obstacle avoidance navigation. The Sugeno fuzzy logic method is used to control the robot's movement decisions based on data received from the sensors, enabling the robot to move adaptively toward the fire source. Once the fire's location is detected, the robot activates a fan as an actuator to extinguish the fire. System testing was conducted by observing the robot's response to the presence of fire, including its ability to detect and extinguish small fires from candles in a short time, as well as navigate obstacles effectively. With this system, it is hoped that it can serve as an initial solution for automatically and efficiently addressing minor fires. Keywords: firefighting robot, Arduino, Sugeno fuzzy logic, flame sensor, automation.